Sistem Pakar Untuk Pertolongan Pertama Gangguan Kesehatan Pada Anak - Pandhega, Prisma Arya, Dedi Gunawan S.T., M.Sc (2016)
The expert system is an attempt to create a system that can perform such a task and as good as an expert. Expert systems can be implemented in various fields such as health, economy, education, olaharaga, even pro-gaming field. In this research, expert systems implemented to diagnose health problems in children. Expert system for health disorders first aid in children can be accessed anywhere and anytime using smartphone users without requiring a data connection. This is certainly very easy for users to perform early diagnosis of the health problems experienced by children. This expert system is designed using Android Studio 1.4 by forward chaining algorithm. Forward chaining algorithm is a tracking methods or facts searching methods started from the left (first IF). In other words, reasoning starts from the facts first to test the truth of the hypothesis. Implementation of this algorithm is copy how a doctor working, that first task is asking the patients about the symptom. Results from this study is a smartphone application that can diagnose health problems in children. This application has been tested and runs well in response to the user's system.